PlantNLRatlas: a comprehensive dataset of full- and partial-length NLR resistance genes across 100 chromosome-level plant genomes - Li, Xiang; Ma, Linna; Wang, Yingmin; Ye, Chen; Guo, Cunwu; Li, Yingbin; Mei, Xinyue; Du, Fei; Huang, Huichuan (Frontiers in Plant Science, 2023)
Plants have evolved two layers of protection against biotic stress, including PAMP-triggered immunity (PTI) and effector-triggered immunity (ETI). The primary mechanism of ETI involves the nucleotide-binding leucine-rich repeat immune receptors (NLRs). Although NLR genes have been studied in several plant species, we are still lacking a comprehensive database of NLR genes across a diverse array of species. Here, we report a comprehensive survey of NLR genes from 100 high-quality plant genomes (PlantNLRatlas), which contain 68,452 full- and partial-length NLRs. Based on the PlantNLRatlas dataset, we found that the domain sequences are highly conserved for each NLR group. The majority of NLR groups were found to cluster into groups according to plant order. Our PlantNLRatlas dataset is complementary to RefPlantNLR, a collection of NLR genes which have been experimentally confirmed. The PlantNLRatlas dataset will be an invaluable resource for the continued study of plant NLRs and for the precision breeding of biotic-stress-resistant crop plants.